A comparative study for the usage of Fidji cervical cages after multilevel anterior cervical discectomy and fusion. Issue 4 (April 2019) - Wang, Ya-peng; Zhang, Wei; An, Ji-long; Lian, Li-chao; Zhang, Jian; Sun, Ya-peng
Highlights: Comparatively large samples of multilevel cervical myelopathy were recruited (n = 62). We prove the application of Fidji cervical cages reduce postoperative dysphagia. This study enriched the literature of Fidji cervical cages on the treatment of ACDF. Abstract: Background: Postoperative dysphagia is one major concern in the treatment for patients with cervical spine spondylosis by using anterior cervical discectomy and fusion (ACDF) with plating and cage system. Purpose: To evaluate the influence of two types of surgery for multilevel cervical spondylotic myelopathy (CSM) on postoperative dysphagia, namely ACDF with cage alone (ACDF-CA) using Fidji cervical cages and ACDF with cage and plate fixation (ACDF-CP). Methods: A retrospective study was performed in 62 consecutive patients with multilevel CSM, including 32 underwent ACDF-CA (group A) and 30 underwent ACDF-CP (group B). All enrolled patients were followed up at 48 h, 2 months and 6 months postoperatively, when the dysphagia rate, Swallowing-Quality of Life (SWAL-QOL) score and the thickness of prevertebral soft tissue were recorded. Results: At 48 h and 2 months, the dysphagia rate and thickness of prevertebral soft tissue were both significantly lower in group A than in group B, while the SWAL-QOL score of group A was significantly higher than that of group B. No significant difference was observed at 6 months. Conclusion: Fidji cervical cages could relieve postoperative dysphagia in the treatment of multilevel CSM with ACDF, especially at the first several months postoperatively.